Adding Value in Production of Multifunctional Polylactide (PLA)–ZnO Nanocomposite Films through Alternative Manufacturing Methods - Marius Murariu; Samira Benali; Yoann Paint; Anne-Laure Dechief; Oltea Murariu; Jean-Marie Raquez; Philippe Dubois (Molecules, 2021)
Due to the added value conferred by zinc oxide (ZnO) nanofiller, e.g., UV protection, antibacterial action, gas-barrier properties, poly(lactic acid) (PLA)–ZnO nanocomposites show increased interest for utilization as films, textile fibers, and injection molding items. The study highlights the beneficial effects of premixing ZnO in PLA under given conditions and its use as masterbatch (MB), a very promising alternative manufacturing technique. This approach allows reducing the residence time at high processing temperature of the thermo-sensitive PLA matrix in contact of ZnO nanoparticles known for their aptitude to promote degradation effects onto the polyester chains. Various PLA–ZnO MBs containing high contents of silane-treated ZnO nanoparticles (up to 40 wt.% nanofiller specifically treated with triethoxycaprylylsilane) were produced by melt-compounding using twin-screw extruders. Subsequently, the selected MBs were melt blended with pristine PLA to produce nanocomposite films containing 1–3 wt.% ZnO. By comparison to the more traditional multi-step process, the MB approach allowed the production of nanocomposites (films) having improved processing and enhanced properties: PLA chains displaying higher molecular weights, improved thermal stability, fine nanofiller distribution, and thermo-mechanical characteristic features, while the UV protection was confirmed by UV-vis spectroscopy measurements. The MB alternative is viewed as a promising flexible technique able to open new perspectives to produce more competitive multifunctional PLA–ZnO nanocomposites.